pH-Regulated Na(+) influx into the mammalian ventricular myocyte: the relative role of Na(+)-H(+) exchange and Na(+)-HCO Co-transport. - Vaughan-Jones, R; Villafuerte, F; Swietach, P; Yamamoto, T; Rossini, A; Spitzer, K (2006)
In the heart, intracellular Na(+) concentration (Na(+) (i)) is a controller of intracellular Ca(2+) signaling, and hence of key aspects of cell contractility and rhythm. Na(+) (i) will be influenced by variation in Na(+) influx. In the present work, we consider one source of Na(+) influx, sarcolemmal acid extrusion. Acid extrusion is accomplished by sarcolemmal H(+) and HCO(3) (-) transporters that import Na(+) ions while exporting H(+) or importing HCO(3) (-). The capacity of this system to import Na(+) is enormous, up to four times the maximum capacity of the Na(+)-K(+) ATPase to extrude Na(+) ions from the cell. In this review we consider the role of Na(+)-H(+) exchange (NHE) and Na(+)-HCO(3) (-)co-transport (NBC) in mediating Na(+) influx into cardiac myocytes. We consider, in particular, the role of NBC, as so little is known about Na(+) influx through this transporter. We show that both proteins mediate significant Na(+) influx and that although, in the ventricular myocyte, NBC-mediated Na(+) influx is less than through NHE, the proportions may be altered under a variety of conditions, including exposure to catecholamines, membrane depolarization, and interference with activity of the enzyme, carbonic anhydrase.